2018
DOI: 10.1093/jee/tox319
|View full text |Cite
|
Sign up to set email alerts
|

Rice Field Spiders in China: A Review of the Literature

Abstract: Many laboratory and field studies have been conducted on rice field spiders in China. There are 375 species, 108 genera, and 22 families of rice field spiders distributed within the major rice growing areas and 17 dominant species. The biological and ecological characteristics of 17 rice field spider species have been reported in detail. The biology and ecology of these species show significant differences among regions, farmland habitats, and agricultural practices. Future research should focus on rice field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 14 publications
0
15
1
Order By: Relevance
“…The diversity as well as the role of spiders in agricultural fields have been documented in several studies (Breene et al 1993;Marc et al 1999;Rajeshwaran et al 2005;Baba et al 2018;Yang et al 2018). They serve as general predators in agricultural ecosystems (Riechert & Bishop 1990) especially in orchard crops associated with diverse pest fauna.…”
Section: Platinum Open Accessmentioning
confidence: 99%
“…The diversity as well as the role of spiders in agricultural fields have been documented in several studies (Breene et al 1993;Marc et al 1999;Rajeshwaran et al 2005;Baba et al 2018;Yang et al 2018). They serve as general predators in agricultural ecosystems (Riechert & Bishop 1990) especially in orchard crops associated with diverse pest fauna.…”
Section: Platinum Open Accessmentioning
confidence: 99%
“…Maternal care in spiders include eggsac construction, eggsac care, and juvenile spiderling care (Ruhland et al 2016b). For example, the web-weaver spiders attach their eggsac to the web, while Lycosidae females carry their eggsac via spinnerets, and then carry the juveniles emerging from eggsac on notum (Yang et al 2018;Yu et al 2022). Egg brooding is effective for offspring protection against predators, parasites, and adverse environment (Iida and Fujisaki 2005;Ruhland et al 2016a; Vieira and Romero 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Although cannibalism is common in the spider, the females do not acutely prey the new-emerged spiderlings during maternal care (Yu et al 2022). P. pseudoannulata females can produce ve eggsacs at most in the life once mating (Yang et al 2018), so the maternal care is alternate with the cannibalism. Ecdysteroids are characterized by their critical roles on arthropods' parental care and cannibalism (Trabalon et al 1998;Vancassel et al 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Despite VgR being well described in many insects and in a few arachnids, it is still unclear in spiders. To take the pond wolf spider Pardosa pseudoannulata as an example, no information relating to VgR is available though it is one of the most dominant predators of pest insects in paddy fields (Yang et al ., 2018). In the present study, we identified and characterized two VgRs in P. pseudoannulata and analyzed the physiological functions of VgR‐1 in reproduction.…”
Section: Introductionmentioning
confidence: 99%